Adenoviral-vectored vaccine against Bordetella pertussis fimbrial antigen induces partial protection in a mouse model - Alexa Dierig; Martina Kristof; Christina Dold; Elodie Lesne; Catpagavalli Asokanathan; Luke Blackwell; Barbara Bolgiano; Andrew R. Gorringe; Andrew J. Pollard; Kevin Markey; Christine S. Rollier (Vaccine: X)
Pertussis has been resurgent in many countries worldwide despite good vaccine coverage. One hypothesis for this resurgence is that the current acellular pertussis (aP) vaccines, used in most developed countries, induce short-term protection, and do not prevent asymptomatic infection and transmission of pertussis infection. As a first step to address these issues we developed novel Bordetella pertussis vaccine candidates using viral-vectored vaccine technology with the aim of producing durable functional antibodies that prevent nasal colonization. Fimbrial antigens Fim2 and Fim3 are protective in mouse models of B. pertussis disease and are included in some aP vaccines. Fim2, Fim3 and FimD were selected, and their genes cloned into entry plasmids for the creation of the corresponding human adenovirus serotype 5 (AdHu5) vectors. Groups of mice were vaccinated with a single dose of either of the three AdHu5 vaccines, or a mixture of them, or control vaccines, which consisted of one or two reduced doses of a whole-cell pertussis vaccine or 5-component aP vaccine. The Fim2 and Fim3 adenovirus-based vaccines and their combinations alone or with FimD induced antigen-specific antibodies, as assessed by whole cell ELISA assay. Strong IgG binding to a Fim3-expressing strain was observed using flow cytometry and these antibodies also mediated complement deposition onto this strain. The AdHu5 Fim3 vaccine induced partial protection against lung infection following aerosol exposure of mice to B. pertussis expressing Fim3. These results indicate that adenovirus vectors have the potential to be effective vaccine platforms for bacterial disease.